(untitled) (Research, Society and Development, 2021)
Schinus terebinthifolius (Anacardiaceae) is among the medicinal species native to Brazil, known as mastic-red and mastic-pepper, whose stem bark is used to fight inflammation of various origins, as it has anti-inflammatory and healing properties. The objective of this study is to explore trends in the publications portrayed on the species S. terebinthifolius, analyzing axes such as time, countries, journals, impact factors and citations, the scientometric approach was used to summarize all the studies on S. terebinthifolius in a single article. 475 publications were used with an average number of 20.8 publications per year, encompassing 68 research areas and published in 220 different journals, covering all retractions visible on the Web of Science from 2001 until May 2021. The most productive country was Brazil with 271 articles, followed by the USA with 105 articles. The methods and results of this study can be applied to continually understand the nature of research on the species.